2010
DOI: 10.1038/ijo.2010.122
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes in early life and future risk of obesity

Abstract: The rapid increase in incidence of obesity over the past two decades cannot be explained solely by genetic and adult lifestyle factors. There is now considerable evidence that the fetal and early postnatal environments also strongly influence the risk of developing obesity in later life. Initially, human studies showed that low birth weight was associated with an increased risk of obesity but increasingly there is evidence that overnutrition in the early life can also increase susceptibility to future obesity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(145 citation statements)
references
References 118 publications
(143 reference statements)
4
137
0
4
Order By: Relevance
“…1,2 In the fetal and early life periods, interactions between biology and environmental exposures produce epigenetic effects that influence the risk of childhood obesity. 3,4 Hence, early life interventions, when both behavior and biology are "plastic," have potential both to ameliorate epigenetic effects and increase resilience to the behavioral and metabolic challenges posed by an obesogenic environment. 1 Early feeding practices likely compound increased obesity risk conferred by genetic predisposition and prenatal factors such as excess gestational weight gain.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In the fetal and early life periods, interactions between biology and environmental exposures produce epigenetic effects that influence the risk of childhood obesity. 3,4 Hence, early life interventions, when both behavior and biology are "plastic," have potential both to ameliorate epigenetic effects and increase resilience to the behavioral and metabolic challenges posed by an obesogenic environment. 1 Early feeding practices likely compound increased obesity risk conferred by genetic predisposition and prenatal factors such as excess gestational weight gain.…”
Section: What This Study Addsmentioning
confidence: 99%
“…50 Established risk factors such as parent weight status, maternal nutrition, excess gestational weight gain, formula feeding, and rapid early weight gain may induce epigenetic processes that in turn increase susceptibility to obesity. 1,3,4 Emerging evidences suggest other heritable infant factors may also confer increased obesity risk. A recent twin study 51 has shown that exclusively breastfed infants at 3 months of age, identified by their mothers as having a big appetite (higher food responsiveness and lower satiety responsiveness), gained more weight from 0 to 15 months, with weight trajectory differences apparent as early as 3 months.…”
Section: Figurementioning
confidence: 99%
“…However the mechanisms by which these loci act on body weight are still largely unknown and may be complicated further by alterations in gene-expression via epigenetic events in specifi c genes (Lillycrop & Burdge, 2011), in addition to alterations to DNA sequence variation. Although a role in general neuronal development has been postulated (Willer et al, 2009), and current attempts to address this issue systematically in adults are largely underpowered, it will be important to evaluate their role in childhood eating behaviours using sophisticated and direct behavioural assessments (Blundell et al, 2009) across specifi c growth points.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Over the last two decades overweight and obesity rates have reached epidemic proportions worldwide, with no evidence that these levels are abating (1)(2)(3) . Globally, obesity rates have almost doubled in adults (2,4,5) and children are also "getting fatter" (6,7) .…”
Section: Introductionmentioning
confidence: 99%